O psicanalista nos cuidados paliativos com crianças - Disaró, Denise Regina (2017)
Palliative care (PC) is a new practice in the world and in Brazil, and even more recent with children. This study was developed in a palliative care setting. Its purpose is to reflect on psychoanalytic care of children in PC, their families, the health team and on the psychoanalyst. With psychoanalysis as a theoretical, technical and ethical reference, a three case study was developed which provided the opportunity to observe how psychoanalytic care occurs in this special condition. The traumatic potential present in the situational dimension tends to cause changes in the Self of the patients and their relatives, who present a psychic functioning and suffering, similar to the psychopathological dimension, such as narcissistic-identity disorders. Through this process, children and their families lose, even temporarily, some important Ego functions to face the circumstances, such as the capacity for mediation, organization, synthesis and integration of the elements present in the situational dimension. This requires that the analyst assume the deficient Ego functions until the people involved gradually rescue the dormant skills. It is as a mediator that the analyst can be a transformational object and enables the psychoanalytic work, the construction of meaning and the elaboration of experience. It is predominantly a more active care with an additional amount of implied presence, although the analyst has to keep, dialectically, the reserved presence which is essential for self-restraint, self-care and to avoid intrusion caused by the excess of implication